Study on Rust Characterization and Prediction of Atmospheric Corrosion Rates for Structural Steels in Yangon (Myanmar) - Khaing, Thinzar; Kyi Win, Yu Yu; Kyaw, Nyan Myint (Institut Teknologi Sepuluh Nopember, 2017)
According to Fontana, â€œCorrosion is defined as the deterioration of a material because of reaction with its environmentâ€. The present study is performed to get the behaviour of rust characterization and to predict long term atmospheric corrosion rates of structural steels in Yangon, Myanmar. Three types of structural steel (Type A, Type B and Type C) samples which are commonly used in Myanmar are exposed outdoors according to BS EN ISO 8565. They are removed one month periods, and their mass losses are determined according to ISO 8407 in Yangon Technological University. At the same time, environmental parameters of the test site are monitored. Rust characterization of structural steels is determined by Scanning Electron Microscopy (SEM) results in University Research Centre (Yangon University, Myanmar). From SEM results, Type A and Type B steels have nearly the same image controlled by Î²-FeOOH which can increase long term corrosion, whereas Type C steel has controlled by Î³-FeOOH. A prediction model is developed using SPSS software to understand the main factors which cause the atmospheric corrosion, and it is found that the atmospheric corrosion in Yangon depends mainly on the time of wetness (TOW